Vivências constitutivas do professor-orientador: entre narciso e minotauro, um legado e uma despedida - Barbosa, Mirian Haubold (2013)
This thesis is inserted in the line of research of Training, Knowledge and Professional Development of the Post-Graduation Program in Education of UFSM. Its theme is the constitutive act of the post-graduation adviser professor, stricto sensu, and focus on the dynamic of the mentoring process seen as a form of legacy and farewell. Its objective is to deepen the comprehension of the personal and professional elaborations of these adviser professors as well as of their constitution, focusing on the integration movements, their cohesion and the consonant expressive conditions. The thesis lies on the epistemic landscape of complexity; it is grounded on interdisciplinary discussions and resorts to the interpretive phenomenological method. The subjects of the thesis are four adviser professors from the Post-Graduation Program in Education, all of them with more than 15 years of teaching experience. Through in-depth interviews, these professors are invited to relate significant experiences to their constitutive and elaborative conceptions as adviser professors and their mentoring style. The relevance of this study is in the investigative exercise that fosters the subjectivity and intersubjectivity as means of deep reflexive processes and in the look at the significance of the human and humanizing transactions, both in the formation of trainers as in the formation of knowledge. It counts with the theoretical support from psychodynamic concepts regarding the personal maturation process and with the contribution of psychology and education, in particular about the interrelation between the personal and professional dimension in the construction of the orientation process. The final reflections are organized in three main lines of analysis that unveil the dynamic under discussion upon the existential experimental optic: in the development of singular historicity; in the development of phenomena that delimitate and condition the internal and external spaces and environments and in the expressivity of the constitutive and elaborative conditions. The interpretative analysis reveals that the dimensions at issue intertwine and condition the continuity of the constitutive process of mentors and mentoring.